Increasing Competitiveness of Creative Business in Small and Medium Enterprises (SMEs): Systematic Literature Review - Edwin Zusrony; Muzakar Isa; Kussudyarsana; Anton Agus Setyawan (JURNAL ILMIAH EDUNOMIKA, 2025)
This study aims to determine the trend of increasing competitiveness of creative businesses in small and medium enterprises (SMEs) in 2018-2024. This research method uses a systematic literature review, which is divided into two steps, namely, planning and implementation of results. This study uses a search approach of 197 relevant articles indexed in the Scopus database, and then a filtering process is carried out until the final results are 20 journals that meet the research criteria, including journal categories, open access categories and full-text manuscripts. The findings show that the competitiveness of creative SMEs is driven by various factors, including organizational adaptation, innovation, knowledge management, institutional support, leadership, and strategic resource management. These determinants interact dynamically to shape SMEs' ability to innovate, adapt, and thrive in competitive markets. Future research should focus on integrating these factors in specific creative sectors to develop a comprehensive framework for enhancing SME competitiveness.